2009
DOI: 10.3989/gya.053709
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing female rats with DHA-lysophosphatidylcholine increases docosahexaenoic acid and acetylcholine contents in the brain and improves the memory and learning capabilities of the pups.

Abstract: DHA has been established. We propose that DHAcontaining lysophosphatidylcholine (DHA-LPC), obtained from DHA-rich eggs may be a suitable form of DHA and choline (the precursor of acetylcholine) supplementation. We evaluated the effectiveness of DHA-LPC to increase DHA and acetylcholine concentration in the brain of pups born from female rats supplemented with DHA-LPC before and during pregnancy. We also evaluated the effect of DHA supplementation on learning and memory capabilities of pups through the Skinner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 62 publications
0
9
0
1
Order By: Relevance
“…A previous study, in which female rats were fed DHA-enriched egg LPC of unknown composition, showed that the pups derived from these animals had increased DHA levels in some brain regions, and exhibited improved operant learning ability 43 , indicating increased passage of DHA through the placenta. However, the brain DHA levels of the mothers were not measured in this study.…”
Section: Discussionmentioning
confidence: 95%
“…A previous study, in which female rats were fed DHA-enriched egg LPC of unknown composition, showed that the pups derived from these animals had increased DHA levels in some brain regions, and exhibited improved operant learning ability 43 , indicating increased passage of DHA through the placenta. However, the brain DHA levels of the mothers were not measured in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Surprisingly, the major accumulation of DHA in placenta of these animals did not lead to a higher DHA status in the offspring. Valenzuela et al (49) showed increased DHA levels in PL fraction of cerebellum and hippocampus of pups at 2 months of age after maternal supplementation during pregnancy with DHA as Lyso-PC in rats. In our study, the level of Lyso-PC was minimal in the diets as Ovolife product contained <3 % of total fat as Lyso-PL, with phosphatidylcholine being the major PL source (64-79 % of total PL).…”
Section: Discussionmentioning
confidence: 99%
“…DHA is concentrated in the phospholipids of neuronal tissues, including hippocampus and cerebellum, which are involved in learning as well as in memory storage [22]. Most recently we demonstrated that DHA supplementation to mother rats during the perinatal period, increases the DHA content of different brain segments of the pups, including hippocampus and cerebellum, and improves the learning and memory capacities of the pups when evaluated through the Skinner box test [23]. As part of the diacylglycerol molecule, DHA may enhance the diacylglycerol-dependent activation of the protein kinase C (PKC) [24].…”
Section: Dha and The Activity Of Neuronal Enzymesmentioning
confidence: 92%